Pendidikan Akhlak Sebagai Ruh Pendidikan Islam - Rahmi Anekasari (Jurnal Hikmatuna, 2017)
The development of a globalized world not only produces human productivity in simplifying your life, but it also has adverse effects on human relations and governance patterns. But of progress emerging globalized moral decadence until today. This fact should not only be a commodity social issues just discourse alone, but should be aware of Indonesia that adult education has lost his soul (moral education / educational character), because it is not stable enough to fortify young people (teenagers) from destructive behaviors they consume from a variety of sources of information. Education should be directed to education that is integrated with the values of faith and piety. Education that can see a multidimensional human beings are not only composed of two elements alone (physical and spiritual). The use of Qur'anic method that is able to see humans as being multidimensional, and five strategies that can be used in education morals / these characters is the integration of faith and piety in the vision, mission, goals and strategies of school; optimization of Islamic religious education in schools is not just a "transfer of knowledge" but "transfer of value"; the integration of faith and piety in the learning process; implementation of extra-minded faith and piety; the formation of school culture that supports the increase of faith and piety; implement the cooperation between the school and parents of students. Education moral / character education by integrating between faith and piety, as well as with various measures and strategies undertaken education is expected to be able to be a bulwark for the youth (teenagers) from destructive behaviors. Until finally able to give birth to a nation that Insan Kamil generation, which is able to carry out their roles and responsibilities both as khalifatullah as well as' abdullah. The young generation that is able to maintain a good relationship with Allah (God hablu min), relationships with fellow human beings (hablu min annas), the relationship with oneself, and the relationship with the environment.